Partially Observed Discrete-valued Time Series - Lakhdar Aggoun; Lakdere Benkherouf; Ali Benmerzouga (Электронное моделирование, 2007)
The analysis of time series of counts is a rapidly developing area. It has very broad application in view of the host of integer-valued time series which cannot be satisfactorily handled within the classical framework of Gaussian- like series. In this paper we derive recursive filters for partially observed discrete-valued time series. These processes are regulated by thinning binomial and multinomial operators (to be defined below). Анализ временных последовательностей отсчетов — интенсивно развивающееся направление. Такой анализ широко используется для базовых целочисленных временных последовательностей, с которыми нельзя удовлетворительно работать в рамках классических последовательностей гауссовa типа. Получены рекурсивные фильтры для частично наблю даемых дискретизированных временных последовательностей. Показано, что эти процессы регулируются прореживающими биномиальными и полиномиальными операторами. Аналіз часових послідовностей відліків — напрям, що інтенсивно розвивається. Такий аналіз широко використовується для базових цілочисельних часових послідовностей, з якими не можна задовільно працювати у рамках класичних послідовностей гаусовa типу. Отримано рекурсивні фільтри для частково спостерігаємих дискретизованих часових послідовностей. Показано, що ці процеси регулюються проріжуючими біноміальними та поліноміальними операторами.